SOMATIC PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK LANGUAGES (Conferencea, 2022)
The culture includes the phraseological units of the language as we can’t imagine any language without one of the parts of phraseological units-somatic words. And every country has its own somatic components of phraseological units. Our research is based on the comparison of English and Uzbek somatic words according to their cross-cultural aspects.